Flexible and Robust Electro‐Optically Responsive Films Based on Novel Silica/Oligoaniline/Carbon Dots Composite. Issue 20 (24th October 2019) - Zhou, Yan; Berda, Erik B.; Ma, Qiang; Liu, Xincai; Wang, Ce; Chao, Danming
Abstract: We report a new electro‐optical composite film based on silica, oligoaniline, and carbon dots prepared by a hydrolytic crosslinking reaction under electrokinetic potentials. The electroactive oligoaniline and fluorescent carbon dots are covalently linked through hydrolysis of siloxane, resulting in multifunctional composite films. The resultant crosslinked architecture endows the films with high flexibility and robust durability. These films display good electrochromic behavior with an obvious color contrast, quick switching rate, and acceptable cycling stability. Moreover, these films reveal an interesting electrofluorochromic performance in continuous potential ranges, attributed to the interaction between oligoaniline and carbon dots, and the change in structure that occurs with changing redox potentials. Further, an enhanced photocurrent response is observed in these materials, as a result of the organic‐inorganic interfaces. Abstract : Lights, camera, action ! A novel flexible and robust electro‐optical composite film is prepared from electroactive oligoaniline and fluorescence carbon dots through an electrochemistry‐assisted hydrolytic crosslinking reaction. The resultant hybrid film displays interesting electro‐optical properties including electrochromism, electrofluorochromism, and photocurrent responsiveness, all directly attributed to the inherent functionality and synergy derived from oligoanilines and carbon dots.